2018
DOI: 10.1007/s10212-018-0406-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions adopting a whole school approach to enhancing social and emotional development: a meta-analysis

Abstract: This article presents findings from a meta-analysis which sought to determine the effectiveness of interventions adopting a whole school approach to enhancing children and young people's social and emotional development. Whole school interventions were included if they involved a coordinated set of activities across curriculum teaching, school ethos and environment, and family and community partnerships. A total of 45 studies (30 interventions) involving 496,299 participants were included in the analysis. Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 42 publications
6
132
1
6
Order By: Relevance
“…Previous research on the impact of SEL interventions on academic outcomes has evidenced small but nonetheless practically meaningful effects (Corcoran et al 2018;Durlak et al 2011;Goldberg et al 2018;Sklad et al 2012;Wigelsworth et al 2016). The null ITT and subgroup findings of the current study may therefore appear incongruous.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Previous research on the impact of SEL interventions on academic outcomes has evidenced small but nonetheless practically meaningful effects (Corcoran et al 2018;Durlak et al 2011;Goldberg et al 2018;Sklad et al 2012;Wigelsworth et al 2016). The null ITT and subgroup findings of the current study may therefore appear incongruous.…”
Section: Discussioncontrasting
confidence: 79%
“…The meta-analyses noted above support these assertions, indicating that SEL interventions have a small but nonetheless practically significant impact on academic performance (effect size ranges from d = 0.19 to d = 0.46) (Corcoran et al 2018;Durlak et al 2011;Goldberg et al 2018;Sklad et al 2012;Wigelsworth et al 2016). However, the evidence base is much less developed than for other domains (e.g.…”
Section: What Is Sel?mentioning
confidence: 94%
See 2 more Smart Citations
“…A meta-analysis of universal social and emotional skill-based interventions found that interventions with a high quality of implementation produced larger expected outcome effect sizes compared with interventions with a low implementation quality (17). A more recent meta-analysis of whole school social and emotional learning programs also found that implementation quality was positively associated with program outcome related effect sizes (22).…”
Section: Introductionmentioning
confidence: 99%